Individual and Social Impacts of Medical Malpractice Complaints on Doctors: A Qualitative Study - Simin Kazemi; Mohammad-Esmaeil Riahi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Medical malpractice lawsuit can persuade physicians to be more careful in practice but each file may have many adverse consequences for doctors and patient and society. The purpose of this study is to investigate the impacts of medical malpractice lawsuit on doctors and their practice. Materials and Methods: This qualitative study conducted by Problem-centered interview and convenience sampling. Participants were 15 physicians who were summoned to Dispute Resolution Council. After declaring the informed consent, a Semi-structured interview was conducted with each doctor. Data was analyzed by encoding and categorization. Results: Psychological consequences include anxiety and depression;   professional effects include time loss and absence from work, social consequence like loss of reputation, family members' concern were the deleterious effects of complaints against physicians. Also changing the practice to defensive medicine is an important consequence of complaints. Conclusion: Patient's complaint can lead to Psychological and social consequences for physicians. Also it can result in defensive medicine that doctors avoid of admitting high risk patients and impose medically unnecessary costs to patients. Investigation of patients' complaints in preliminary expert commissions and before calling doctors to judicial authorities can help reduce these problems